Weight reduction as a non-pharmacological treatment method for type 2 diabetes - Borek, Mikołaj (Nursing Problems / Problemy Pielęgniarstwa, 2025)
Type 2 diabetes is a chronic metabolic disease strongly associated with overweight and obesity. Weight reduction is a crucial com-ponent of the non-pharmacological treatment for this condition, improving insulin sensitivity, β-cell function, and lipid metabolism. This paper explores the epidemiology of type 2 diabetes, the relationship between excessive adipose tissue and metabolic disorders, and the benefits of weight loss. Studies show that a weight reduction of 5-10% significantly improves metabolic control, while a loss exceeding 15 kg can lead to disease remission. Lifestyle changes, including diet, physical activity, and psychological support, play a key role in treatment. However, long-term outcomes depend on patient commitment and access to comprehensive medical care.